Literature review: The utilization of tomatoes (Solanum lycopersicum) and lidah buaya (Aloe vera) in cosmetic applications - Wibowo, Diki Prayugo; Rahma, Siti; Herawati, Irma Erika; Mariani, Ria (Institute of Computer Science (IOCS), 2023)
The popularity of herbal cosmetics has been growing due to their effectiveness and ability to reduce the adverse effects associated with the use of synthetic goods. Plants contain phytochemicals like alkaloids, flavonoids, saponins, sterols, triterpenoids, and tannins, which give them many health benefits, such as antioxidant activity, anti-inflammatory effects, UV protection, skin regeneration, depigmentation, anti-dandruff properties, and more. Plants like tomatoes and Aloe vera contain phytochemicals that can be used in cosmetics. We want to give you all the information you need about how tomatoes and Aloe vera might be used in cosmetics. This includes what chemicals they contain, how they work biologically, and how to make cosmetics with them. This article review employs online literature studies as its methodology. The research data comprises articles sourced from reputable journal platforms, including Google Scholar, PubMed, Science Direct, and Research Gate. These articles were selected from publications spanning the period from 2013 to 2023. The research that has already been done supports the idea that both tomatoes and Aloe vera contain many chemicals that could be used in cosmetic treatments.